Vitamin D Deficiency and the Risk of Cerebrovascular Disease - Hyun Ah Kim; Andrea Perrelli; Alberto Ragni; Francesca Retta; T. Michael De Silva; Christopher G. Sobey; Saverio Francesco Retta (MDPI AG, 2020)
Vitamin D deficiency has been clearly linked to major chronic diseases associated with oxidative stress, inflammation, and aging, including cardiovascular and neurodegenerative diseases, diabetes, and cancer. In particular, the cardiovascular system appears to be highly sensitive to vitamin D deficiency, as this may result in endothelial dysfunction and vascular defects via multiple mechanisms. Accordingly, recent research developments have led to the proposal that pharmacological interventions targeting either vitamin D deficiency or its key downstream effects, including defective autophagy and abnormal pro-oxidant and pro-inflammatory responses, may be able to limit the onset and severity of major cerebrovascular diseases, such as stroke and cerebrovascular malformations. Here we review the available evidence supporting the role of vitamin D in preventing or limiting the development of these cerebrovascular diseases, which are leading causes of disability and death all over the world.